HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP PERILAKU PENYALAHGUNAAN NARKOBA PADA SISWA/I SMP NEGERI 4 KECAMATAN PONTIANAK TIMUR KOTAMADYA PONTIANAK TAHUN 2013 - ., Yeli Asti (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Illicit drug behavior is used drug for non medical purposes,produced, trafficked, and/ or consumed illicitly. Adolescents aresusceptible groups for illicit drug users. This research aims to find theassociation between knowledge toward attitude, knowledge towardbehavior, and attitude toward illicit drug behavior of SMP Negeri 4 EastPontianak District in 2013. Method: This is an analytic study with crosssectionalapproach used stratified random sampling. Data was obtainedfrom the questionnaire filled by 265 student (102 sample for VII grade, 22sample for VIII grade, and 91 sample for IX grade). Data processed byusing chi-square test. Results: There was significant association betweenattitude toward illicit drug behavior (p=0,03). There were no significantassociation both between knowledge toward attitude (p=0,1) andknowledge toward behaviuor (p=0,7). Conclusion: Association betweenattitude toward behavior were influenced by norms, cultures, and groups.